Hypermethylated LTR retrotransposon exhibits enhancer activity. Issue 3 (4th March 2017) - Hu, Tianxiang; Zhu, Xingguo; Pi, Wenhu; Yu, Miao; Shi, Huidong; Tuan, Dorothy
ABSTRACT: LTR retrotransposons are repetitive DNA elements comprising ∼10% of the human genome. They are silenced by hypermethylation of cytosines in CpG dinucleotides and are considered parasitic DNA serving no useful function for the host genome. However, hypermethylated LTRs contain enhancer and promoter sequences and can promote tissue-specific transcription of cis -linked genes. To resolve the apparent paradox of hypermethylated LTRs possessing transcriptional activities, we studied the ERV-9 LTR retrotransposon located at the 5′ border of the transcriptionally active β -globin gene locus in human erythroid progenitor and erythroleukemia K562 cells. We found that the ERV-9 LTR, containing 65 CpGs in 1.7 kb DNA, was hypermethylated (with > 90% methylated CpGs). Hypermethylated LTR possessed transcriptional enhancer activity, since in vivo deletion of the LTR by CRISPR-cas9 suppressed transcription of the globin genes by > 50%. ChIP-qPCR and ChIP-seq studies showed that the hypermethylated LTR enhancer spanning recurrent CCAATCG and GATA motifs associated respectively with key transcription factors (TFs) NF-Y and GATA-1 and -2 at reduced levels, compared with the unmethylated LTR in transfected LTR-reporter gene plasmids. Electrophoretic mobility shift assays with methylated LTR enhancer probe showed that the methylated probe bound both NF-Y and GATA-1 and -2 with lower affinities than the unmethylated enhancer probe. Thus, hypermethylation drastically reduced, but did not totally abolish, the binding affinities of the enhancer motifs to the key TFs to assemble the LTR-pol II transcription complex that activated transcription of cis -linked genes at reduced efficiency.